Exploring the Usage of ChatGPT in Higher Education: Frequency and Impact on Productivity - Radha Firaina; Dwi Sulisworo (Buletin Edukasi Indonesia, 2023)
This research aims to gain a deeper understanding of the views and rationality of lecturers in using ChatGPT in learning by explaining how lecturers use it in learning and their reasons for choosing or not choosing the technology. In this study, lecturers will be interviewed and asked to share their experiences and views on it. The data collected will be analyzed and interpreted to gain a deeper understanding of how the use of ChatGPT affects learning and why lecturers choose or do not choose the technology. In the interview results, ChatGPT helps users in finding information, ideas, translating texts, and providing alternative questions to deepen the understanding of the material. It is important to consider and verify information with more reliable and accurate sources. The use of ChatGPT in learning can be an interesting and effective alternative, but users also need to remain critical and selective in utilizing it. In further research, more interviews and case studies need to be conducted to obtain a more comprehensive understanding of the use of ChatGPT in learning. Although ChatGPT has limitations, respondents consider its use to improve productivity and learning efficiency. Therefore, the use of ChatGPT can be considered as an attractive alternative in learning, while maintaining a critical approach in utilizing it and verifying the information provided.